Biologically active polyketides produced by Penicillium janthinellum isolated as an endophytic fungus from fruits of Melia azedarach - MARINHO, Andrey Moacir do Rosário (2015)
Penicillium janthinellum, isolated as an endophytic fungus from fruits of Melia azedarach, was cultivated over 20 days on ground and autoclaved white corn, where the known polyketides citrinin, emodin, 1,6,8-trihydroxy-3-hydroxymethylanthraquinone, and a new modified anthraquinone, named janthinone, were produced and isolated by classical chromatographic procedures and identified by MS and 1D and 2D NMR spectroscopic data. The antibacterial properties of these polyketides were investigated. Citrinin inhibited 100% of Leishmania growth after 48h at a concentration of 40 μg mL-1.